PENERAPAN MODEL PEMBELAJARAN PENCAPAIAN KONSEP UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII PADA MATERI HIMPUNAN DI MTs. NURUL HASANAH PENGAWU - Widiastuti, Widiastuti (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
The objective of this research is to obtain a description in the implementation of design of learning to get concept which can increase the study value of students’ grade VII on the set material at MTs. Nurul Hasanah Pengawu. This reseacrh used Classroom Action Research, that based on Kurt lewin design.is planning, action, observation and reflection. The result of this research  showed  the used  of learning to get concept which can increase the one come  of student grade VII on the set material through 3  fase, that is: (1)  presentation and identification of data,(2) examined of concept and (3) strategies analyze.